Escherichia coli has robust regulatory mechanisms against elevated peptidoglycan cleavage by lytic transglycosylases - Liang, Yaquan (2024)
Peptidoglycan (PG) is an essential and conserved exoskeletal component in all bacteria that protects cells from lysis. Gram-negative bacteria such as Escherichia coli encode multiple redundant lytic transglycosylases (LTs) that engage in PG cleavage, a potentially lethal activity requiring proper regulation to prevent autolysis. To elucidate the potential effects and cellular regulatory mechanisms of elevated LT activity, we individually cloned the periplasmic domains of two membrane-bound LTs, MltA and MltB, under the control of the arabinose-inducible system for overexpression in the periplasmic space in E. coli. Interestingly, upon induction, the culture undergoes an initial period of cell lysis followed by robust growth restoration. The LT-overexpressing E. coli exhibits altered morphology with larger spherical cells, which is in line with the weakening of the PG layer due to aberrant LT activity. On the other hand, the restored cells display a similar rod shape and PG profile that is indistinguishable from the uninduced control. Quantitative proteomics analysis of the restored cells identified significant protein enrichment in the regulator of capsule synthesis (Rcs) regulon, a two-component stress response known to be specifically activated by PG damage. We showed that LT-overexpressing E. coli with an inactivated Rcs system partially impairs the growth restoration process, supporting the involvement of the Rcs system in countering aberrant PG cleavage. Furthermore, we demonstrated that the elevated LT activity specifically potentiates β-lactam antibiotics against E. coli with a defective Rcs regulon, suggesting the dual effects of augmented PG cleavage and blocked PG synthesis as a potential antimicrobial strategy.